Different applications of Scheffler reflector for renewable energy: a comprehensive review. Issue 6 (11th May 2020) - Panchal, Hitesh; Patel, Jay; Parmar, Kiran; Patel, Mayank
Abstract : A fixed focus on receiver maintains constant temperature of receiver and it is achieved by Scheffler reflector. It is a best example of solar energy application used for medium-temperature applications. The present review shows a complete review of Scheffler reflector in solar thermal applications like desalination, coffee-making machine, agricultural application, electricity generation, hot water, cooking and plaster of Paris production. The Scheffler reflector is a best solar energy application in future emerging technologies.